KOPERASI INDONESIA: PRINSIP DAN KECENDERUNGAN (Studi Kasus 4 KUD Mandiri Di Daerah Istimewa Yogyakarta) - hudiyanto, hudiyanto (Jurnal Ekonomi & Studi Pembangunan, 2002)
Cooperative as an economic institution mandated by pasal 33 UUD 1945 tend to be seen in negative perception. This is related to an uncapability of the cooperative in wheeling business activities because of the strong role of government in developing cooperative. Cooperative often imaged as in agent and apparatuses of government. This article attempt to know cooperative performance especially in case of Koperasi Unit Desa (KUD) Comprise four KUD Mandiri.